A Case of Eosinophilic Esophagitis Accompanying Familial Mediterranean Fever - Pejman Rohani; Mehri Najafi Sani; Mitra Ahmadi; Vahid Ziaee (Case Reports in Gastrointestinal Medicine)
Background. Eosinophilic esophagitis is an inflammatory condition where there is a dense infiltration of eosinophils typically exceeding fifteen cells per high power field. Familial Mediterranean fever is an autosomal recessive disorder characterized by brief, acute, and self-limited episodes of fever and polyserositis that recur at irregular intervals. Case Presentation. A three-year-and-nine-month-old Iranian girl was admitted to our center. The patient’s parents complained of a history of abdominal pain, poor appetite, and poor weight gain from 1.5 years ago and episodes of food impaction after starting solid foods. Eosinophilic esophagitis was diagnosed based on histology. Because of continuing abdominal pain after treatment of eosinophilic esophagitis, the episodic nature of disease, and the presence of fever with pain, screening for familial Mediterranean fever mutation was performed and the patient was found to be heterozygote for Mediterranean fever. Conclusion. We have reported a case of eosinophilic esophagitis coexisting with familial Mediterranean fever which has not been described previously.